Thinking through the environment green approaches to global history - Myllyntaus, Timo (White Horse Press, 2011)
"Thinking through the Environment: Green Approaches to Global History" is a collection offering global perspectives on the intersections of mind and environment across a variety of discourses - from history and politics to the visual arts and architecture. As the title suggests, the volume exposes the lenses - tinted by culture and history - through which humans consider environments; and also foregrounds the importance of rigorous 'thinking through' of the lessons of environmental history and the challenges of the environmental future.